2022
DOI: 10.1182/bloodadvances.2021006147
|View full text |Cite
|
Sign up to set email alerts
|

A new role for the SRC family kinase HCK as a driver of SYK activation in MYD88 mutated lymphomas

Abstract: The SRC family kinase (SFK) HCK is transcriptionally upregulated and activated by mutated MYD88 (MYD88Mut), a key adaptor for Toll-receptor signaling. HCK activates BTK, AKT and ERK in MYD88Mut lymphomas. SYK, a BCR component is activated in MYD88Mut lymphoma cells. While the SFK LYN serves as a trigger for SYK activation in MYD88Mut ABC DLBCL cells, LYN activity is muted in MYD88Mut WM cells. We therefore investigated a role for HCK in mediating SYK activation. Over-expression of wild-type (HCKWT) or gatekeep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among them, FCGR3A and FCGR3B genes encode Fcγ receptors, which are expressed on neutrophils and bind to immune complexes and activate neutrophils to participate in immune responses. SYK and HCK genes encode tyrosine kinases, which are involved in biological processes such as neutrophil signaling, cell proliferation and differentiation, and cell adhesion [57].The PTPRC (also known as CD45) gene encodes a protein tyrosine phosphatase, which is responsible for regulating the activity of intracellular signaling pathways [58]. ITGAM (also known as CD11b) gene encodes integrin, which interacts with integrin β2 (ITGB2, also known as CD18) to form integrin αMβ2 (also known as Mac-1 or CD11b/CD18) on the surface of neutrophils, which is involved in processes such as cell adhesion, migration and phagocytosis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, FCGR3A and FCGR3B genes encode Fcγ receptors, which are expressed on neutrophils and bind to immune complexes and activate neutrophils to participate in immune responses. SYK and HCK genes encode tyrosine kinases, which are involved in biological processes such as neutrophil signaling, cell proliferation and differentiation, and cell adhesion [57].The PTPRC (also known as CD45) gene encodes a protein tyrosine phosphatase, which is responsible for regulating the activity of intracellular signaling pathways [58]. ITGAM (also known as CD11b) gene encodes integrin, which interacts with integrin β2 (ITGB2, also known as CD18) to form integrin αMβ2 (also known as Mac-1 or CD11b/CD18) on the surface of neutrophils, which is involved in processes such as cell adhesion, migration and phagocytosis [59].…”
Section: Discussionmentioning
confidence: 99%
“…The SRC-family tyrosine kinase (SFK) hematopoietic cell kinase (HCK), which is predominantly expressed in the hematopoietic cell lineage, has been implicated in various cellular processes including inflammation, proliferation and actin polymerization [17][18][19][20]. We have recently shown that HCK is aberrantly upregulated in MCL patients and that high HCK expression correlates with poor clinical outcome [21].…”
Section: Introductionmentioning
confidence: 99%